Geom(et)oda [rec. Anna Kronenberg: Geopoetyka. Związki literatury i środowiska. Łódź: Wydawnictwo Uniwersytetu Łódzkiego, 2014, ss. 288.] - Kadłubek, Zbigniew (Śląskie Studia Polonistyczne, 2015)
In the wake of spacial turn, we are currently observing in literature a growing interest in space, of which geopoetics is one aspect. The book Geopoetyka. Związki literatury i środowiska by Anna Kronenberg was submitted as her doctoral dissertation at the Department of Theory of Literature, Institute of Contemporary Culture at the University of Łódź. The author is known for her interest in geopoetics, ecocriticism, ecofeminism and Polish immigration literature. The reviewer of Kronenberg’s work focuses on the geopoetical value of the young researcher from Łódź. She is praised for the metaphorical character of her study and her involvement reaching far beyond the academia. On the other hand however, it is pointed out that she is unable to develop Kenneth White’s thought in the scientific discourse, as compared with Elżbieta Rybicka who does so on assumption so to speak.